(untitled) (Journal of Pakistan Orthopaedic Association, 2013)
Objective: To study the various trends in treatment followed by patients suffering from Primary Osteo-Arthritis attending the outpatient clinics. Study Design: Case Series Place and Duration of study: Liaqat National Hospital, Karachi - From October to December 2012 Patients and Methods: This was an observational study in which a random set of 263 patients suffering from primary Osteo arthritis (who had not undergone any surgical intervention) was selected from the Medical and Rheumatology outpatient clinics of Liaqat National Hospital Karachi. Both males and females were included. Their ages ranged from 30 years to 80 years and their treatment trends were studied. Results: Out of 263 patients, 70 were males and 193 were females. The largest number of patients i.e. 85 was in the age group of 50-60 years and the smallest number of patients i.e. 14 was in the age group of 70-80 years. Oral medication was the mainstay of treatment and was being taken by all the patients, either alone or in combination with intra articular injections ( IAI’s ) and/or physical therapy. Oral medication comprised of NSAIDS, Glucosamine and Chondroitin Sulphate, Calcium and Vitamin D supplements. All the patients were taking NSAIDS either alone or in combination with Glucosamine and Chondroitin Sulphate and/or Calcium and Vitamin D. Conclusion: The main treatment trend in our patients was: Oral medication, being used alone or in combination with intra articular injection and/or physical therapy. NSAIDS were the mainstay of treatment used by all the patients, either alone or in combination with Glucosamine and Chondroitin Sulphate and/or Calcium and Vitamin D supplements. None of them had undergone any patient education regarding the disease or lifestyle modification.